Kewajiban Menuntut Ilmu dalam Perspektif Hadis - Darani, Nurlia Putri (Jurnal Riset Agama, 2021)
The purpose of this study is to discuss how the explanation of the hadith about the obligation to study. This research method uses a qualitative type through literature study with content analysis. The results and discussion of this study include the meaning of studying, takhrij hadith about the obligation to study, and how the ethics of a student in studying. The conclusion of this study shows that the command to study is an obligation and the hadith that explains the obligation to study is a saheeh hadith. This study recommends the importance of understanding among Muslims about their obligations in studying.